SKRINING FITOKIMIA DAN UJI ANTIOKSIDAN EKSTRAK DAUN KANGKUNG PAGAR (Ipomoea carnea Jacq) - Ermi Abriyani; Lia Fikayuniar; Arie wichandar (Jurnal Buana Farma, 2023)
The Kangkung pagar (Ipomea carnea Jacq) leaves the one source of antioxidant activity. This plant is used as traditional medicine and has potensially anti-oxidant, anti-microbial, immunostimulant, anti-cancer, liver protector and many pharmacological activities. Antioxidant can neutralize of free radicals by inhibiting the occurrence of oxidant. The aim of this study to determine of result of phytochemical screening, antioxidant activity by DPPH and FRAP methods. Methods of this study are phytochemicals screening, extraction of Ipomea carnea Jacq leave by maceration with ethanol 96%., antioxidant assays by DPPH and FRAP by determine EC50 value and the absorbances from spectroscopy UV Vis. . The result of phytochemicals screening are appear of alkaloids, flavonoids, terpenoids, steroids, saponins and tannins and antioxidants assays result EC50 value by FRAP methods were n-hexane (27.08 ppm, ethyl acetate 55.53 ppm, ethanol 68.23 ppm. While the results EC50 by DPPH methods were n-hexane 71.89 ppm, ethyl acetate 48.31 ppm and ethanol 41.07 ppm. It concluded that ipomea carnea Jacq. It can be concluded that the leaves of Ipomea carnea Jacq are a potensial source of antioxidants.